2016
DOI: 10.1108/nlw-09-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between citation counts and Mendeley readership metrics

Abstract: Purpose – Social media has given way for the development of various new altmetric indicators. Mendeley readership count is one such indicator. The purpose of this paper is twofold. First, the paper aims to investigate the relationship between citation counts and Mendeley readership counts. The paper also evaluates the relationship between Mendeley readership metrics for two different time periods, thereby investigating its nature as an altmetric indicator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…On the one hand, this has important benefits with respect to accessibility of knowledge, but on the other, it has potential to further skew rankings. It is likely that open access material will benefit from higher citations than similar standard work that is not immediately made available (Shrivastava and Mahajan, 2016). Open access has to be paid for and universities or researchers themselves are having to pay for this privilege.…”
Section: Research and Business School Rankingmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, this has important benefits with respect to accessibility of knowledge, but on the other, it has potential to further skew rankings. It is likely that open access material will benefit from higher citations than similar standard work that is not immediately made available (Shrivastava and Mahajan, 2016). Open access has to be paid for and universities or researchers themselves are having to pay for this privilege.…”
Section: Research and Business School Rankingmentioning
confidence: 99%
“…Time is needed for citations to accumulate (Gruber, 2014) and they can be gamed and manipulated (self-citation can be problematic here), and they can artificially reward prolific authors of mediocre papers, Finch (2010). Additionally, groups of researchers may cite each other in order to inflate citation counts (Shrivastava and Mahajan, 2016).…”
Section: Citation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Similar research in which metrics from specific platforms (Mendeley, ResearchGate, Twitter, CiteULike) are compared with traditional sources of bibliometrics (generally Scopus or Web of Science) to establish the presence or absence of correlation between traditional bibliometrics and altmetrics are being performed systematically. 11,12,16,[19][20][21][22][23] The Life Sciences post publication peer review site F1000 has been shown to have strong correlations between citations and F1000 article rankings in a cluster of studies. 18 Generally there is little correlation between cited references and altmetrics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Twitter for instance, skews young and urban while Mendeley skews academic. 19,35 Depending upon the desired outcome for the professor's research, a specific platform may be a wiser venue for alternative scholarly communication, which will in turn drive the disciplinary professor to select a different altmetric.…”
Section: Matching Social Media Channels To Altmetric Toolsmentioning
confidence: 99%